Effect of pentagamavunon-O on rat kidney’s glutathione s-transferase in-vivo with 1-chloro-2, 4-dinitro benzene as a substrate - Rohman, Abdul; Martono, Sudibyo; A. Margono, Supardjan (Indonesian Journal of Pharmacy, 2004)
Glutathione S-transferase (GST) is a detoxifying enzyme which plays an important role in glutathione conjugation reaction with electrophilic xenobiotic on phase two metabolism. In this research, the effect of oral administration of PGV-0 on rat kidney’s GST activity was investigated.To represent GST activity isolated from rat kidney, 1-chloro-2,4-dinitro benzen (CDNB) was used as a substrate on conjugation with glutathione (GSH) spectrophotometrically. The activity of rat kidney’s GSTs from untreated rat was used as control, Based on data, it can be concluded that PGV-0 showed an inhibitory effect on rat kidney’s GSTs. The optimum effect was obtained at 40 mg/kgBW with % inhibition value of 16,16.Key words : Pentagamavunon-0, Glutathione S-transferase, 1-chloro-2,4-dinitro benzene